A Software Tool for the Measurement of the Aortic Annulus Area by Means of Computed Tomography Image Analysis for the Planning of Transcatheter Aortic Valve Replacement (TAVR) - Hervas, Gloria Campos; Cisnal, Agustin Fernandez; Garcia-Blas, Sergio; Minana, Gema; Valero, Ernesto; Sanchis, Juan; Moratal, David (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
Cardiovascular diseases (CVD) are the leading cause of death globally, being the heart valve complications one of the five most common heart problems. The aim of this study is the development of a MATLAB-based software tool to obtain several measurements derived from the aortic annulus for the planning of transcatheter aortic valve replacement (TAVR). The proposed software tool utilizes computed tomography (CT) images to reconstruct a volume of the patient. This virtual volume is rotated to situate the images in the plane which cuts the most basal points of the three aortic valve cusps, namely the aortic annulus, and obtain the required measurements. Nevertheless, the computer-user interaction will be entirely based on 2-dimension techniques to reduce both the complexity of the app and the computational load. The program was validated in CT images of 10 subjects with diagnosed aortic stenosis. A comparison of the results with the measurements used in the real clinical practice showed no significant differences between both methods.Clinical Relevance- The resulting computer tool provides significant information about the diseased aortic valve. This will allow clinicians to select the right prosthetic heart valve. It represents a cheaper and less complex alternative to sophisticated software tools which are currently being used to plan the intervention.